Factors that influence the customers towards the selection in Islamic home financing: a case study in Selangor / Munirah Shafiqah Mansor - Mansor, Munirah Shafiqah (Faculty of Business Management, 2017)
The study investigates on the importance of factors that influence the selection in Islamic home financing among customers in Selangor. This study is conduct the relationship between reputation, social influence, service quality, religious belief and media advertisement and factor influence customer selection towards Islamic home financing. There are 150 questionnaire are prepare and distribute to the targeted respondents in the Selangor area. Only 136 respondents out of 150 answered the questionnaire accordingly. This employed Pearson correlation and multiple regression method to achieve the objective. Findings show that there was significant positive correlation selection of Islamic home financing with reputation, social influence, service quality, religious obligation and media advertisement. It recommend that, Islamic provider need to play an important role in order to attract customers to use Islamic home financing product. Therefore, analysis presented in this research can be used for the future researcher that related with this study.